The Effect of Early and Delayed Harvest on Dynamics of Fermentation Profile, Chemical Composition, and Bacterial Community of King Grass Silage - Long, Shihe; Li, Xuefeng; Yuan, Xianjun; Su, Rina; Pan, Junxin; Chang, Ye; Shi, Mengli; Cui, Zhihai; Huang, Naixin; Wang, Jian (Frontiers in Microbiology, 2022)
This study assessed the effect of harvesting time on the fermentation characteristics, chemical composition, and microbial community of King grass silage. King grass at three growth periods of 90 d (KN90S), 110 d (KN110S), and 130 d (KN130S) were harvested and ensiled. Silages were sampled after 1, 3, 7, 14, 30, and 60 d of ensiling for fermentation and chemical composition analyses. Bacterial community was profiled in silage ensiled for 60 d. The KN110S showed the most rapid pH decline and lactic acid production during 7 d of fermentation. After 60 d of fermentation, the KN110S showed the lowest pH and the highest lactic acid content among the 3 treatments. The butyric acid and ammonia nitrogen contents of KN90S and KN130S were significantly greater than those of KN110S (p < 0.05). A higher relative abundance of Clostridium was observed in KN90S and KN130S, but not in KN110S. The fermented quality observed in natural King grass silage with a growth period of 110 d is better than those early harvested with 90 d of growth or harvested at late with 130 d of growth, and there is a need to utilize additives to optimize the fermentation quality of King grass.